Антология выдающихся достижений в науке и технике. Часть 30: Портрет харьковского математика, механика и кибернетика Владимира Логвиновича Рвачева - Баранов, Михаил Иванович (НТУ "ХПИ", 2016)
Приведен краткий научно-исторический очерк об известном ученом-математике Харьковщины − академике АН УССР (НАН Украины) Рвачеве В. Л. и о его выдающемся вкладе в мировую математическую науку.

Description of basic scientific achievements, features of personality and way of life of the known Kharkov mathematician, mechanical engineer and cyberneticist, academician of NAS of Ukraine Rvachev V. L. in the short form is presented.
An anthology of the distinguished achievements in science and technique. Part 30: Portrait of the Kharkov mathematician, mechanical engineer and cyberneticist Vladimir Logvinovich Rvachev
Keywords: история; выдающиеся научные достижения; Харьковский политехнический институт; Институт проблем машиностроения; history; distinguished scientific achievements